A Review of the Research on the Influencing Factors of Lubrication Performance for Sliding Bearings - Yu, Xiaodong; Zhan, Shiwei; Huang, Dianbin; Sun, Fan; Wang, Fakun; Han, Fei; Zhao, Yan (Recent Patents on Engineering, 2022)
Background: Sliding bearing is a kind of bearing that works under sliding friction, which has the characteristics of stable operation, safety and reliability, and is noiseless. With the technological progress of the machinery industry, modern machinery and equipment is developing in the direction of high speed and heavy load, its power is getting higher and higher, and the working environment is getting worse, so plain bearings are more and more widely used. Objective: In order to improve the lubricating performance of sliding bearings, the influencing factors of the lubricating performance of sliding bearings are summarized and commented on. Methods: The research progress and achievements at home and abroad are summarized from three aspects: influencing factors of lubrication performance of radial sliding bearings, thrust sliding bearings, and influencing factors of lubricating oil on lubrication performance of sliding bearings, which provides reference for the future development of sliding bearings. Results: The study discusses the experimental method, simulation process, and experimental results of the factors affecting the lubrication performance of sliding bearing. Conclusion: The texture, deformation, surface morphology of oil cavity, eccentric load, and flow state of sliding bearings all affect the lubricating performance of sliding bearings, and lubricating oil also affects the lubricating performance of sliding bearings.
Keywords: offset load